Privatisation as a Tenet of Growth Employment and Redistribution Strategy and its Socio-Economic Impact on the Poor in Khayelitsha - Joao M Domingos; William Fox (European Scientific Journal, ESJ, 2018)
This paper seeks to present the macro-economic impact of privatisation in the Western Cape as perceived by its proponents and detractors, nationally and internationally. It investigates the effects and factors which influence privatisation. The study was conducted in the township of Khayelitsha. The sites were randomly selected and included Site C, Site B, ElithaPark, Macassar and MandelaPark. An in-depth literature review was conducted to investigate the macro-economic policy of Growth Employment and Redistribution Strategy (GEAR) and its tenet, privatisation. The socio-economic impacts of privatisation on the Khayelitsha communities were investigated by posing four questions. The researcher employed qualitative and quantitative research methodology to establish the opinions of the participants. Two types of data analysis were used namely: structural and interpretational. These techniques were appropriate for the study because they explored the feelings of the recipients of government policies. The result of the study revealed that privatisation is not creating jobs as expected and that economic growth does not benefit the poor. The research revealed the financial inability of the people to afford basic services. The Khayelitsha community prefer services rendered by government instead of the private sector. The findings of the statistical analysis indicated the respondents’ dissatisfaction with government’s privatisation objectives. The researchers concludes that it is necessary to take into account that government in principle has the interests of the citizens at heart. However, its macro-economic policy is not having the desired results.